Teori Imperialisme Baru dan Debat Marxisme-Realisme dalam Ilmu Hubungan Internasional - Alvian, Rizky Alif (UI Scholars Hub, 2016)
This paper aims to discuss the contribution of new imperialism theory for International Relations. This contribution will be analyzed by positing new imperialism theory in the light of Marxism-Realism debate. This debate is centered on the question on how the relation between state and mode of production should be formulated. While Realism tends to underestimate the role of mode of production in international relations, Marxism tends to underestimate the role of state. This paper argues that new imperialism theory could be understood as an experiment to resolve this issue. By separating “economy”/”the logic of capitalism” from “politic”/”the logic of territorial”, new imperialism theory attempts to reconcile the role of state and mode of production in the analysis of international relations.